Attitudes toward Refugees in Contemporary Europe: A Longitudinal Perspective on Cross-National Differences. (24th June 2020) - Czymara, Christian S
Abstract: In 2015, the number of people seeking asylum in Europe skyrocketed. However, asylum applications were mainly concentrated in a few destination countries such as Germany, Austria, or Sweden. After the so-called EU-Turkey deal, asylum rates quickly dropped in subsequent years. I examine how these developments affected public opinion from both a static and a dynamic comparative perspective. The rapid and largely unpredicted rise in refugee numbers and their prominence in public debates make demographic changes potent drivers of out-group hostility. The analysis of data from over 50, 000 individuals in 22 countries contained in the seventh and eighth waves of the European Social Survey shows that attitudes toward refugees do not simply follow trends in asylum applications. Significantly lowering refugee numbers, hence, did not counter anti-refugee sentiments in the European public. Based on intra-country variation over time, the model rather predicts an increase in negative attitudes during times of considerable demographic shifts. Deeper analyses reveal that this effect is stronger for conservative Europeans as well as for those who distrust EU-politics. Moreover, while a general willingness to help is associated with more openness toward refugees, actually experiencing foreigner inflow diminishes this link, suggesting limitations of humanitarian concerns. Results are stable across various modelling and sample choices and not driven by individual countries. In sum, these findings demonstrate the importance of temporal dynamics for the formation of attitudes toward refugees in contemporary Europe and point to potentially polarizing effects of immigration along ideological lines.